2000
DOI: 10.1099/00221287-146-10-2531
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa mediated apoptosis requires the ADP-ribosylating activity of ExoS

Abstract: Pseudomonas aeruginosa is an opportunistic bacterial pathogen that primarily infects immunocompromised individuals and patients with cystic fibrosis. Using a tissue culture system, invasive strains of P. aeruginosa were discovered to induce apoptosis at high frequency in HeLa and other epithelial and fibroblast cell lines. This apoptotic phenotype in the infected cells was determined by several criteria including (i) visual changes in cell morphology, (ii) induction of chromatin condensation and nuclear margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
148
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 49 publications
(41 reference statements)
6
148
1
Order By: Relevance
“…The amino-terminal GAP activity acts on Rho family GTPases while the carboxylterminal ADPRT activity is directed towards Ras and other host-cell proteins (Fraylick et al, 2001;Goehring et al, 1999;Henriksson et al, 2000Henriksson et al, , 2002Krall et al, 2002;Olson et al, 1999;Rocha et al, 2003;Vincent et al, 1999). As a result of these enzymic activities, intoxication with ExoS is associated with several observable phenotypes, including cytotoxicity and inhibition of bacterial internalization by both phagocytic and non-phagocytic mammalian cells (Cowell et al, 2000;Fleiszig et al, 1997;Frithz-Lindsten et al, 1997;Henriksson et al, 2000;Kaufman et al, 2000;Olson et al, 1997Olson et al, , 1999Pederson & Barbieri, 1998;Vincent et al, 1999). (Throughout this discussion, the term 'cytotoxicity' will be used to refer to cytolytic cell death.)…”
Section: Introductionmentioning
confidence: 99%
“…The amino-terminal GAP activity acts on Rho family GTPases while the carboxylterminal ADPRT activity is directed towards Ras and other host-cell proteins (Fraylick et al, 2001;Goehring et al, 1999;Henriksson et al, 2000Henriksson et al, , 2002Krall et al, 2002;Olson et al, 1999;Rocha et al, 2003;Vincent et al, 1999). As a result of these enzymic activities, intoxication with ExoS is associated with several observable phenotypes, including cytotoxicity and inhibition of bacterial internalization by both phagocytic and non-phagocytic mammalian cells (Cowell et al, 2000;Fleiszig et al, 1997;Frithz-Lindsten et al, 1997;Henriksson et al, 2000;Kaufman et al, 2000;Olson et al, 1997Olson et al, , 1999Pederson & Barbieri, 1998;Vincent et al, 1999). (Throughout this discussion, the term 'cytotoxicity' will be used to refer to cytolytic cell death.)…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that T3S effectors from P. aeruginosa are responsible for inducing rapid apoptosis is macrophage cells and epithelial cells (Hauser and Engel 1999;Kaufman, Jia et al 2000). Prior results in this study indicated down regulation of …”
Section: Dhl Treated Pseudomonas Aeruginosa and Apoptosissupporting
confidence: 57%
“…It is well known that ExoS preferentially ADP-ribosylates several Ras family members (GTP-binding proteins) required for the regulation of intracellular vesicle transport, cell proliferation and differentiation (Coburn & Gill, 1991;Ganesan et al, 1998). The ADP-ribosyltransferase activity of ExoS has also been shown to be essential in triggering programmed cell death in various types of tissue-culture cells (Kaufman et al, 2000;Jia et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ExoS preferentially ADP-ribosylates several Ras family members (GTP-binding proteins) required for the regulation of intracellular vesicle transport, cell proliferation and differentiation (Coburn & Gill, 1991;Ganesan et al, 1998). The ADP-ribosyltransferase activity of ExoS has also been shown to be essential in triggering programmed cell death in various types of tissue-culture cells (Kaufman et al, 2000; Jia et al, 2003).The type III secretion complex of P. aeruginosa is highly similar to that of members of the genus Yersinia and, when expressed in cells of this genus, the ExoS protein can be translocated into mammalian cells via the yersinia TTSS (Frithz-Lindsten et al, 1997, 1998. Both organisms harbour multiple regulators to tightly control the expression of the large type III secretion gene clusters in response to lowcalcium environmental stimuli.…”
mentioning
confidence: 99%
See 1 more Smart Citation